MANAGEMENT AND LEADERSHIP - Lukić, Zoran; Mustafić, Amela; Došenović, Dragana (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2015)
The topic of the paper is the management process in enterprises, particularly focused on leadership as one of the basic managerial functions or activities. In order to achieve the preset objectives, it is necessary to appoint a number of people who would successfully lead the company and its employees, and, consequently, facilitate its efficient operation. For that reason, the purpose of the paper is to describe the processes of management and leadership, as well as to emphasize their importance in achieving positive business results. Given the importance and the role that managers and leaders have in the functioning of any organization, the paper shall present their similarities and differences, i.e. similarities and differences between the processes they perform in various organizations. Based on the assessment and the analysis conducted, the paper provided numerous conclusions on the basis of which it has been proved that there are significant differences between management and leadership. In order for a manager to be successful in performing his tasks, it is most frequently required of him to be the leader at the same time, thus emphasizing the importance of leadership as a management activity required for the successful operation and achievement of the objectives of any organization.